Analisis Keberagaman Input Produksi Usahatani Tembakau Kabupaten Bojonegoro dengan Pendekatan Multivariat Cluster - Jannatun Naim; Moh Yusuf Dawud; Noor Djohar (Jurnal MeA (Media Agribisnis), 2026)
The plantation sector plays a strategic role in the national economy. Tobacco is one of the leading commodities that contributes to national economic development. This is evidenced by the tobacco industry, which employs an average of 47,840 people. Bojonegoro Regency is one of the largest tobacco producers in East Java Province, but crop productivity tends to fluctuate. This is due to the diversity of production inputs used by farmers. This study aims to group tobacco farmers based on their patterns of production input use. The approach used in this study is multivariate cluster analysis with the K-means algorithm. The method used in this study is descriptive quantitative with primary data collection through questionnaires to 100 tobacco farmer respondents from six sub-districts using the Simple Random Sampling technique. The sub-districts were selected based on the largest tobacco production in descending order, starting from Kepohbaru, Kedungadem, Baureno, Sugihwaras, Sukosewu, and Temayang. The variables analyzed included land area, number of seedlings, amount of fertilizer, labor, pesticides, and capital. The data were processed through Z-score standardization and analyzed using the K-Means Clustering algorithm with the help of SPSS software. The determination of the optimal number of clusters was validated using the Elbow and Silhouette Coefficient methods. The characteristics of the farmers revealed that the majority of tobacco farmers in Bojonegoro were of productive age (51-60 years) with considerable farming experience (16-25 years), but in terms of education, they were predominantly elementary school graduates with relatively small land holdings (≤0.5 Ha). The grouping of tobacco farmers using K-means clustering is expected to form groups of farmers based on patterns of production input use so that the results of this study can be used as a reference in the formulation of agricultural policies.